(untitled) (Bangladesh Journal of Botany, 2011)
Effects and possible interaction of elevated CO2 and water stress on the stomatal morphology and the pattern of gas exchange in leaves of eggplants (Solanum melongena L. cv. Senryo No. 2) were investigated. Sedlings were grown to maturity in controlled growth chamber using ambient CO2 (365 370 ppm) and elevated CO2 (700 ppm) and at frequent watering as control and watering after every 21 days for simulating periodic water stress and recovery from stress. A complementary acclimatisation of photosynthesis in water stressed eggplants grown under elevated CO2 was evident. Despite decreased stomatal conductance and transpiration rate under elevated CO2 conditions, increased net leaf photosynthesis rate was observed. Stomatal length and width decreased under water stress and increased CO2. Key words: Water stress; Adaptation; Eggplant; Gas exchange; Stomatal density; Transpiration rate DOI: http://dx.doi.org/10.3329/bjb.v40i1.7985 Bangladesh J. Bot. 40(1): 1-8, 2011 (June)